Corruption in the education sector in Indonesia: Reality, causes, and solutions - Sidik Permana; Mursyid Setiawan (Integritas: Jurnal Antikorupsi, 2024)
Corruption within Indonesia’s education sector ranks among the most frequently identified and prosecuted cases by the Corruption Eradication Commission (KPK). Education itself is a vital sector for human resource development; therefore, corruption within it poses a direct threat to the development process. This concern forms the foundation for this study, which aims to analyze the current realities, causes, and solutions to address corruption in Indonesia’s education sector. The findings of this article may serve as strategies to mitigate and prevent potential corruption within this critical sector. This study employs a literature review with a qualitative approach, drawing primarily on data from books, journals, institutional reports, accredited websites, and other relevant documents. Data analysis was conducted after compiling and reviewing various literature sources, from which insights and conclusions were derived. The results reveal a pervasive corruption problem in the education sector, supported by diverse data points. The causes of corruption are multifaceted, encompassing personal motives, societal and cultural influences, weak law enforcement and oversight, government negligence, and inadequate institutional management. Consequently, the proposed solutions are categorized into three dimensions: individual/personal, environmental/cultural, and institutional.